Exploitation of the nonlinearities in electromagnetic energy harvesting and passive UHF RFID. Issue 1 (22nd February 2016) - Andia-Vera, Gianfranco; Nawale, Shankar; Duroc, Yvan; Tedjini, Smail
Abstract : In this paper, some theoretical aspects and experimental results are discussed with the aim to provide supplementary dc energy to radio frequency identification (RFID) tags by exploiting the nonlinear nature of rectifier devices. Three nonlinear phenomena are treated: (i) the impedance power dependence, (ii) the harmonic production, and (iii) the dependence on the radio frequency waveform. The novelty of the work relies on proposing a double rectifier composite system in where the nonlinearity of each rectifier is exploited to enhance the global powering performance of the system. Using the passive RFID technology as a beacon for the implementation, the approach considers combining the internal rectifier circuit of a commercial RFID chip operating at 868 MHz with an external rectifier circuit operating at 2.17 GHz. The solution triggers in a composite system RFID tag-harvester integrated in a single-feed dual-band antenna. The experimental validation shows 5 dB of tag sensitivity enhancement when it is empowered by the external harvester. The enhanced sensitivity produces an increase in the theoretical reading range distance from 3.3 to 6.1 m.